Стандарти Організації економічного співробітництва та розвитку щодо урегулювання лобіювання - Нестерович, В.; Nesterovych, V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто стандарти Організації економічного співробітництва та розвитку щодо урегулювання лобіювання. Ця міжнародна організація постійно здійснює досить помітні заходи щодо впровадження міжнародних стандартів у сфері регулювання лобіювання та їх імплементації на національному рівні країнами-учасницями. Головним лейтмотивом такої уваги Організації економічного співробітництва і розвитку до просування ідеї законодавчого регулювання лобіювання на національному рівні є насамперед запобігання корупції при прийнятті нормативно-правових актів. The article considers Standards of Organization for Economic Cooperation and Development (OECD) concerning the settlement of lobbying issues. Attention is paid to the ten principles of the Organization for Economic Cooperation and Development to ensure transparency and integrity in lobbying, which are grouped into four parts. The first part deals with the creation of an efficient and equitable framework for transparency and access. The second part of principles is aimed at increasing the transparency of lobbying, the third part – the culture of the integrity of lobbying and the fourth – mechanisms for effective implementation, compliance and consideration in the sphere of lobbying. Organization for Economic Cooperation and Development constantly carries out noticeable and fairly manifold measures to implement internationalstandards into regulation of lobbying issues and their implementation at a national level of the member-countries of this international organization. The main reason for this attention of Organization for Economic Cooperation and Development to the issue is to promote the idea of legal regulation of lobbying atthe national level which can provide basis for preventing corruption in the legislative processes as one of the most dangerous challenges for a democratic system of governance. For our state it would be extremely useful to join the initiatives of the Economic Cooperation and Development, which undoubtedly will strengthen their democratic adjustments in Ukraine in the context of European aspirations of the Ukrainian people.
Standards of the Organization for Economic Cooperation and Development (OECD) Concerning the Adjustment of Lobbying.
Keywords: Організація економічного співробітництва та розвитку; урегулювання; лобіювання; лобіст; прозорість; Organization for Economic Cooperation and Development; regulation; lobbying; lobbyist; transparency